Pediatric nursing clinical guide - Kyle, Terri; Carman, Susan (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
Suitable for students and practicing nurses to use in pediatric patient care, this title includes nursing management for frequently encountered childhood illnesses and disorders, common diagnostic tests and nursing procedures, and a section for principles of nursing care in children